Emotional Independence and Its Relationship to Coping Skills among University Students - Khalaf, Mohammed Mahmoud (Journal of Tikrit University for Humanities, 2025)
The aim of the research was to identify emotional independence and its relationship to coping competence among university students. The sample consisted of 300 students from the College of Education for Humanities at Tikrit University. The researcher constructed a scale for emotional independence consisting of 30 items and a scale for coping competence consisting of 24 items. The researcher verified their validity and reliability and presented them to a group of experienced and specialized people in the field of educational and psychological sciences. After transcribing the data, the researcher reached a number of results, including: the average scores of emotional independence included in the research are less than the hypothetical average of the scale, which means that the research sample has a low level of emotional independence. There is also a statistically significant difference according to the gender variable among students (males, females) in favor of males on the scale prepared for this purpose. In light of these results, recommendations are presented, including specialists should hold seminars on emotional independence and coping competence and their impact on the academic level of students.